One-carbon metabolism and global DNA methylation in mothers of individuals with Down syndrome - Mendes, Cristiani Cortez; Zampieri, Bruna Lancia; Arantes, Lidia Maria Rebolho Batista; Melendez, Matias Eliseo; Biselli, Joice Matos [UNESP]; Carvalho, André Lopes; Eberlin, Marcos Nogueira; Riccio, Maria Francesca; Vannucchi, Hélio; Carvalho, Valdemir Melechco; Goloni-Bertollo, Eny Maria; Pavarino, Érika Cristina (Springer Nature, 2021)
Down syndrome (DS) is the most common chromosomal disorder, resulting from the failure of normal chromosome 21 segregation. Studies have suggested that impairments within the one-carbon metabolic pathway can be of relevance for the global genome instability observed in mothers of individuals with DS. Based on the association between global DNA hypomethylation, genome instability, and impairments within the one-carbon metabolic pathway, the present study aimed to identify possible predictors, within the one-carbon metabolism, of global DNA methylation, measured by methylation patterns of LINE-1 and Alu repetitive sequences, in mothers of individuals with DS and mothers of individuals without the syndrome. In addition, we investigated one-carbon genetic polymorphisms and metabolites as maternal predisposing factors for the occurrence of trisomy 21 in children. Eighty-three samples of mothers of children with DS with karyotypically confirmed free trisomy 21 (case group) and 84 of mothers who had at least one child without DS or any other aneuploidy were included in the study. Pyrosequencing assays were performed to access global methylation. The results showed that group affiliation (case or control), betaine-homocysteine methyltransferase (BHMT) G742A and transcobalamin 2 (TCN2) C776G polymorphisms, and folate concentration were identified as predictors of global Alu DNA methylation values. In addition, thymidylate synthase (TYMS) 28-bp repeats 2R/3R or 3R/3R genotypes are independent maternal predisposing factors for having a child with DS. This study adds evidence that supports the association of impairments in the one-carbon metabolism, global DNA methylation, and the possibility of having a child with DS.
Keywords: Alu elements; DNA methylation; Down syndrome; Long interspersed nucleotide elements; Polymorphism, Genetic